Genetic diversity and SNP's from the chloroplast coding regions of virus-infected cassava - De Marchi, Bruno Rossitto [UNESP] (2020)
Cassava is a staple food crop in sub-Saharan Africa; it is a rich source of carbohydrates and proteins which currently supports livelihoods of more than 800 million people worldwide. However, its continued production is at stake due to vector-transmitted diseases such as Cassava mosaic disease and Cassava brown streak disease. Currently, the management and control of viral diseases in cassava relies mainly on virus-resistant cultivars of cassava. Thus, the discovery of new target genes for plant virus resistance is essential for the development of more cassava varieties by conventional breeding or genetic engineering. The chloroplast is a common target for plant viruses propagation and is also a potential source for discovering new resistant genes for plant breeding. Non-infected and infected cassava leaf samples were obtained from different locations of East Africa in Tanzania, Kenya and Mozambique. RNA extraction followed by cDNA library preparation and Illumina sequencing was performed. Assembling and mapping of the reads were carried out and 33 partial chloroplast genomes were obtained. Bayesian phylogenetic analysis from 55 chloroplast protein-coding genes of a dataset with 39 taxa was performed and the single nucleotide polymorphisms for the chloroplast dataset were identified. Phylogenetic analysis revealed considerable genetic diversity present in chloroplast partial genome among cultivated cassava of East Africa. The results obtained may supplement data of previously selected resistant materials and aid breeding programs to find diversity and achieve resistance for new cassava varieties.